Instagram-Based School Marketing Communication and Students School Choice Decisions: The Mediating Role of Brand Image - Berry Aulia Fatah; Veranus Sidharta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study examines the influence of Instagram-based school marketing communication on students' school choice decisions, with school brand image as a mediating variable. Using an explanatory quantitative approach, data were collected through a cross-sectional survey of 150 students at SMAN 3 South Jakarta who had seen or were aware of the school's Instagram content. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The measurement model showed that all indicators met the criteria for convergent validity, construct reliability, and discriminant validity. The structural model revealed that Instagram-based school promotion had a positive and significant effect on school brand image and students' school choice decisions. School brand image also had a positive and significant effect on students' decisions. Furthermore, the indirect effect test confirmed that brand image partially mediated the relationship between Instagram promotion and school choice decisions. These findings indicate that Instagram functions not only as an informative promotional channel but also as a strategic communication medium for shaping school image, strengthening students' perceptions, and influencing educational decision-making